THE USE OF FIGURATIVE LANGUAGES IN THE INAUGURAL SPEECH OF BARACK OBAMA - Athin Anajulya Pungkasari; Mahyuni Mahyuni; Nuriadi Nuriadi; Kamaludin Yusra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the figurative language used in Barack Obama’s second inaugural address, focusing on its types, semantic meanings, and pragmatic functions. Taking a qualitative descriptive approach, the research uses Perrine’s classification of figurative language, alongside semantic theory and pragmatic theory as analytical frameworks. Data were taken from the official transcript and video recording of the speech and analyzed using Miles, Huberman, and Saldaña’s content analysis model. The results revealed 32 figurative expressions, consisting of 13 metaphors, 6 personifications, 6 hyperboles, 5 synecdoches, and 2 symbols. Semantically, these expressions extend literal meanings into richer, more symbolic ones that emphasize themes of equality, unity, and progress. Pragmatically, they inspire, persuade, and unify the audience by presenting complex issues in a clear and emotionally engaging manner. However, as the study is limited to a single speech, the findings cannot fully represent figurative language in political discourse as a whole. Nevertheless, the study shows that figurative language was central to Obama’s rhetorical strategy, functioning not only as a stylistic device but also as a persuasive tool that reinforced shared values and legitimized leadership. Keywords: figurative language, inaugural speech, Barack Obama